Manipulation of Spectral Hole Burning in Atomic Medium by Doppler Broadening Effect - Zahid Noor,; Samiur Rahman,; Najeeb Ullah,; Muhammad Umair, (Dialogue Social Science Review (DSSR), 2024)
Spectral holes burning are controlled and modified in a four-level sodium hot atomic medium. Two spectral holes are measured in the absorption spectrum, which are associated with steep normal dispersive regions. The group velocity is slowed down in this normal dispersive region from vacuum speed vg << c. The spectral hole occurs at the phase pc — T/ 2 with equal depths and equal normal dispersion on both sides of the resonance point. The spectral hole occurs at the phase pc < T/ 2 with unequal depths and unequal normal dispersion on both sides of the resonance point. The depth of the spectral hole at the negative detuning is smaller, and the spectral hole at positive detuning is larger when pc < n/ 2, while it shows contrasting behavior at pc > T/ 2. This work shows significant variation in spectral holes with the collective phase of control fields and the corresponding enhanced and degraded steepness of normal dispersion in the regions of spectral holes burning.